2016
DOI: 10.1007/s00590-016-1839-y
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal shock wave therapy, ultrasound-guided percutaneous lavage, corticosteroid injection and combined treatment for the treatment of rotator cuff calcific tendinopathy: a network meta-analysis of RCTs

Abstract: Treatment of calcific tendinitis using extracorporeal shock wave therapy (ESWT), ultrasound-guided percutaneous lavage (UGPL or barbotage), subacromial corticosteroid injection (SAI) and combined treatment is still controversial. This systematic review and meta-regression aimed to compare clinical outcomes between treatments. Relevant RCTs were identified using PubMed and Scopus search engines to date of September 23, 2015. Seven of 920 studies identified were eligible. Compared to the other treatments, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 40 publications
5
31
2
3
Order By: Relevance
“…Meta-analyses have shown that the ESWT administration in calcific tendinitis leads to decreasing VAS scores. [20] In our study, a clinical improvement similar to the calcific tendinitis was demonstrated with the ESWT application in non-calcific tendinitis.…”
Section: Discussionsupporting
confidence: 71%
“…Meta-analyses have shown that the ESWT administration in calcific tendinitis leads to decreasing VAS scores. [20] In our study, a clinical improvement similar to the calcific tendinitis was demonstrated with the ESWT application in non-calcific tendinitis.…”
Section: Discussionsupporting
confidence: 71%
“…However, a substantial number of patients has persisting symptoms requiring other therapies such as subacromial injections with corticosteroids, needle aspiration of calcific deposits (NACD), or extracorporeal shockwave therapy (ESWT) [5]. A recently published meta-analysis comparing these therapies concluded that NACD is the most effective treatment considering relevant clinical outcomes within a follow-up term of 2 years [6]. However, up to 42% of patients experience persisting or recurrent shoulder complaints after NACD [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…There is 1 study that described success with minimally invasive ultrasound‐guided procedures, such as synovial cyst aspiration and corticosteroid injection for various rheumatic diseases, including gout [11]. To our knowledge, there has not been research published regarding ultrasound‐guided needle barbotage or percutaneous lavage for the treatment of intratendinous tophaceous gout, although multiple randomized controlled studies demonstrate improved outcomes from ultrasound‐guided percutaneous lavage in calcific tendonitis of the rotator cuff [12].…”
Section: Discussionmentioning
confidence: 99%